Zmiany globalne jako czynnik rozwoju lokalnego - Ponikowski, Henryk (Global Changes as a Factor of Local Development, 2007)
The paper presents characteristic features of relations between global changes and local development. It indicates that multi-layer networks of territorial phenomena have a system of non-linear dependence in practice. Therefore, global changes are perceived as factors of local development. For the purpose of modeling dependence between global changes and local development, it is possible to make use of approach based on feed-forward artificial neural networks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 237-247